El baile de la loquera: the Carnival Aspect of Danceable Music Practice of Mosh and Slam for the Urban Youth in Costa Rica during the Decade of 1990, the Case of Ska Music - Hernández Parra, Sergio Isaac (2022)
This article discusses the danceable music practice of “mosh” and “slam” as a form of subversive attitude for the urban youth, based on the carnival theory of Mijail Bajtin. In particular, proposes a transdisciplinary methodology based in the analysis of social discourse, discographic production and ethnographic data. All this allows to achieve the following objective: analyze the carnivalesque form in the danceable practice of “ska” music for Costa Rican urban youth during the decade of 1990.